Additional Information on the Building History of the Premonstratensian Provost Church in Zsámbék Based on the Art Forms and an Investigation of the Wall Structure - Bozóki, Lajos (Acta Historiae Artium Academiae Scientiarum Hungaricae, 2025)
Keywords: zsámbék

Reviving heritage: Renovation beckons for Hungary’s oldest Church in Zsámbék - Kusnyerik, Emma (Daily News Hungary, 2024)
Keywords: zsámbék

„Tekintsd e művet, Isten”. A zsámbéki premontrei templom és kolostor története - Valter, Ilona (Martin Opitz Kiadó, 2023)
Keywords: zsámbék

Detecting short-term weathering of stone monuments by 3D laser scanning: lithology, wall orientation, material loss - Fehér, Krisztina; Török, Ákos (Journal of Cultural Heritage, 2022)
Stone deterioration is a non-linear process that is difficult to observe in a short period. The current study documents surface changes related to material loss using terrestrial laser scanner (TLS) and explains the differences in weathering of lithotypes and different wall orientations of various weathering forms. Ruins of a medieval church constructed from weathering-prone porous limestone were surveyed prior to and after a winter period in a five-month interval with two scan phases. Thirty-five stone surfaces of exposed and sheltered wall sections of different compass orientations were compared to assess the short-term material loss and weathering. The study revealed that more than 30% of the selected surfaces show a major surface retreat of more than 4 mm. Three to nine percent of the scanned areas show countable deterioration. The most significant material loss was recorded at rain exposed but partially wind protected walls facing Northeast. Lithology also controls the surface loss and the rate of weathering. Ooidal porous limestone is the most sensitive lithology to weathering. The minor heterogeneities of the stone ashlar and the co-existence of weathered and seemingly intact areas even within one stone block were also considered. Comparing two time-lapses allows for recognizing even minor surface loss. Scans could be made before and after the weathering threshold, but it cannot be predicted when the threshold is reached.
Keywords: zsámbék

A zsámbéki premontrei templom középkori falfestményeiről egy 1895. évi restaurátori árajánlat alapján - Fehér, Ildikó (900 éves a premontrei rend : tanulmányok a rend magyarországi történetéről, kulturális és művelődéstörténeti jelentőségéről, 2022)
Keywords: zsámbék

A zsámbéki premontrei templom 13. századi boltozatai - Fehér, Krisztina (900 éves a premontrei rend : tanulmányok a rend magyarországi történetéről, kulturális és művelődéstörténeti jelentőségéről, 2022)
Keywords: zsámbék

Késő gótikus boltozat az egykori zsámbéki premontrei prépostság épületében - Szőke, Balázs (900 éves a premontrei rend : tanulmányok a rend magyarországi történetéről, kulturális és művelődéstörténeti jelentőségéről, 2022)
Keywords: zsámbék

A zsámbéki prépostság története a hitelesítő ásatás tükrében - Valter, Ilona (900 éves a premontrei rend : tanulmányok a rend magyarországi történetéről, kulturális és művelődéstörténeti jelentőségéről, 2022)
Keywords: zsámbék

Remarks on the Proportions and Dimensions Used in the Design of the Medieval Church of Zsámbék - Fehér, Krisztina; Halmos, Balázs (Periodica Polytechnica Architecture, 2019)
Since the 19th century, the church of Zsámbék was continuously a focus of scholars' interest. The present paper intends to research the church ruins with a new aspect. Using an accurate terrestrial laser scan survey, the geometry of the plan is analysed in order to find proportions among the dimensions. The main goal of the study is to gather information about the design logic of the first masters of the 13th-century Premonstratensian abbey. In addition, our goal was to detect contributions to the 13th-century construction history of the church, that cannot be found in archives of graphic sources. The latest archaeological excavation achieved excellent results concerning several crucial historical points; however, the periodization of the church is still not entirely clarified. From the 19th century, different scholars have proposed various hypotheses about this topic, without consensus.
Number: 2
Keywords: zsámbék

Zsámbéki premontrei prépostsági templom - Szakács, Béla Zsolt (Magyar muvelodéstörténeti lexikon: középkor és kora újkor, 2012)
Keywords: zsámbék

Zsámbék elfeledett falképei: Giovanni Battista Cavalcaselle tanítványának felmérése a premontrei templom falképeiről 1895-ből - Fehér, Ildikó (Művészettörténeti Értesítő, 2008)
The forgotten frescoes of Zsámbék. The assessment of the frescoes of the Premonstratensian church by a pupil of Giovanni Battista Cavalcaselle in 1895
Keywords: zsámbék

Die Werkstattbeziehungen der romanischen Kirche am Zsámbék - Guzsik, Tamás (Alba Regia, 1976)
Keywords: zsámbék

A zsámbéki templomrom. A premontreiek egykori Keresztelő Szent Jánosról nevezett préapostsági temploma - Lux, Géza (Szerzői kiadás, 1939)
Keywords: zsámbék

Die Kirchenruine von Zsambek in Ungarn - Weiß, Karl (Mittheilungen der K.K. Central-Commission für Erforschung und Erhaltung der Kunst- und Historischen Denkmale, 1857)
Keywords: zsámbék